17α-Estradiol Modulates IGF1 and Hepatic Gene Expression in a Sex-Specific Manner. (28th August 2020) - Sidhom, Silvana; Schneider, Augusto; Fang, Yimin; McFadden, Samuel; Darcy, Justin; Sathiaseelan, Roshini; Palmer, Allyson K; Steyn, Frederik J; Grillari, Johannes; Kopchick, John J; Bartke, Andrzej; Siddiqi, Shadab; et al.
Abstract: Aging is the greatest risk factor for most chronic diseases. The somatotropic axis is one of the most conserved biological pathways that regulates aging across species. 17α-Estradiol (17α-E2), a diastereomer of 17β-estradiol (17β-E2), was recently found to elicit health benefits, including improved insulin sensitivity and extend longevity exclusively in male mice. Given that 17β-E2 is known to modulate somatotropic signaling in females through actions in the pituitary and liver, we hypothesized that 17α-E2 may be modulating the somatotropic axis in males, thereby contributing to health benefits. Herein, we demonstrate that 17α-E2 increases hepatic insulin-like growth factor 1 (IGF1) production in male mice without inducing any changes in pulsatile growth hormone (GH) secretion. Using growth hormone receptor knockout (GHRKO) mice, we subsequently determined that the induction of hepatic IGF1 by 17α-E2 is dependent upon GH signaling in male mice, and that 17α-E2 elicits no effects on IGF1 production in female mice. We also determined that 17α-E2 failed to feminize the hepatic transcriptional profile in normal (N) male mice, as evidenced by a clear divergence between the sexes, regardless of treatment. Conversely, significant overlap in transcriptional profiles was observed between sexes in GHRKO mice, and this was unaffected by 17α-E2 treatment. Based on these findings, we propose that 17α-E2 acts as a pleiotropic pathway modulator in male mice by uncoupling IGF1 production from insulin sensitivity. In summary, 17α-E2 treatment upregulates IGF1 production in wild-type (and N) male mice in what appears to be a GH-dependent fashion, while no effects in female IGF1 production are observed following 17α-E2 treatment.